2016
DOI: 10.5001/omj.2016.78
|View full text |Cite
|
Sign up to set email alerts
|

Is the Ratio of Antibodies Against Oxidized LDL to Oxidized LDL an Indicator of Cardiovascular Risk in Psoriasis?

Abstract: Our results suggest that an elevated ratio of anti-ox-LDL/ox-LDL can serve as a composite parameter reflecting the total oxidative lipoprotein burden and cardiovascular risk in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
2
9
0
2
Order By: Relevance
“…Among 45 patients with moderate psoriasis severity (mean PASI: 14.0 ±8.3), Sunitha et al found a correlation between the PASI and anti-oxLDL and oxLDL concentrations. Moreover, compared to controls, patients with psoriasis had a higher anti-ox-LDL : oxLDL ratio, which indicated greater oxidative stress [ 32 ]. Patients with psoriasis were found to have oxLDLs in the epidermis and serum [ 5 , 8 , 11 , 24 , 25 , 32 ], as well as antibodies against HDLs or apolipoprotein AI [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 45 patients with moderate psoriasis severity (mean PASI: 14.0 ±8.3), Sunitha et al found a correlation between the PASI and anti-oxLDL and oxLDL concentrations. Moreover, compared to controls, patients with psoriasis had a higher anti-ox-LDL : oxLDL ratio, which indicated greater oxidative stress [ 32 ]. Patients with psoriasis were found to have oxLDLs in the epidermis and serum [ 5 , 8 , 11 , 24 , 25 , 32 ], as well as antibodies against HDLs or apolipoprotein AI [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It showed that the anti-ox-LDL/ox-LDL ratio correlated significantly with disease severity, its levels increasing linearly with increasing severity. 35 Nakhwa et al did not find a statistically significant correlation between PASI score determined severity of disease and lipid profile abnormalities. At the same time, they found a reduced HDL-C level in patients with severe form of psoriasis.…”
Section: Discussionmentioning
confidence: 92%
“…Chronic inflammation in psoriatic lesions affects the formation of reactive oxygen species (ROS) leading to 'oxidative stress.' 45 They cause damage to endothelial cells, increase permeability of small blood and allow the migration of inflammatory cells. Oxidative stress increases the production of eicosanoids (by activation of phospholipase A) which have proinflammatory and chemoattractant properties.…”
Section: Cyclitols and Oxidative Stressmentioning
confidence: 99%